# SOLUTION: 5x + 3y = -10 3x + 5y= -6 how do you solve the system of equations by elimination

Algebra ->  Coordinate Systems and Linear Equations -> SOLUTION: 5x + 3y = -10 3x + 5y= -6 how do you solve the system of equations by elimination      Log On

 Ad: You enter your algebra equation or inequality - Algebrator solves it step-by-step while providing clear explanations. Free on-line demo . Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Mathway solves algebra homework problems with step-by-step help!

 Linear Solvers Practice Answers archive Word Problems Lessons In depth

 Click here to see ALL problems on Linear-systems Question 268761: 5x + 3y = -10 3x + 5y= -6 how do you solve the system of equations by eliminationAnswer by persian52(158)   (Show Source): You can put this solution on YOUR website!5x+3y=-10_3x+5y=-6 =►Multiply each equation by the value that makes the coefficients of x equal. This value is found by dividing the least common multiple of the coefficients of x by the current coefficient. In this case, the least common multiple is 15. 3*(5x+3y=-10)_5*(3x+5y=-6) =►Multiply each equation by the value that makes the coefficients of x equal. This value is found by dividing the least common multiple of the coefficients of x by the current coefficient. In this case, the least common multiple is 15. 3*(5x+3y)=3(-10)_5*(3x+5y)=5(-6) =►Multiply 3 by each term inside the parentheses. 3*(5x+3y)=-30_5*(3x+5y)=5(-6) =►Multiply 3 by each term inside the parentheses. (15x+9y)=-30_5*(3x+5y)=5(-6) =►Remove the parentheses around the expression 15x+9y. 15x+9y=-30_5*(3x+5y)=5(-6) =►Multiply 5 by each term inside the parentheses. 15x+9y=-30_5*(3x+5y)=-30 =►Multiply 5 by each term inside the parentheses. 15x+9y=-30_(15x+25y)=-30 =►Remove the parentheses around the expression 15x+25y. 15x+9y=-30_15x+25y=-30 =►Multiply the first equation by -1 to make the coefficients of x have opposite signs. -(15x+9y)=-(-30)_15x+25y=-30 =►Multiply -1 by the -30 inside the parentheses. -(15x+9y)=30_15x+25y=-30 =►Multiply -1 by each term inside the parentheses. (-15x-9y)=30_15x+25y=-30 =►Remove the parentheses around the expression -15x-9y. -15x-9y=30_15x+25y=-30 =►Add the two equations together to eliminate x from the system. 15x+25y=-30_-15x-9y=30_ 16y= 0 =►Divide each term in the equation by 16. y=0 =►Substitute the value found for y into the original equation to solve for x. -15x-9(0)=30 =►Multiply -9 by each term inside the parentheses. -15x+0=30 =►Remove the 0 from the polynomial; adding or subtracting 0 does not change the value of the expression. -15x=30 =►Divide each term in the equation by -15. x=-2 =►This is the final solution to the independent system of equations. y=0_x=-2